Studi Komparatif Pemberian Air Susu Ibu (ASI) dan Glukosa 30% terhadap Respon Nyeri Neonatus yang Dilakukan Tindakan Invasif di Rumah Sakit Abdul Moeloek Provinsi Lampung - Sri Suharti (Politeknik Kesehatan Tanjung Karang, 2017)
Neonates that were hospitalized, often got invasive procedure that causes pain. Invasive procedures in 54 neonates that were in the NICU, there were occur 3283 times acts that cause pain during treatment. Pain is an unpleasant experience due to tissue damage, that have subjective nature can be assessed from facial expressions, body movements, crying and break. The pain scale were using the Neonatal Infant Pain Scale (NIPS). This study was to compare the combination of breast feeding and NNS to combination glucose 30% and NNS, for neonatal pain response during applying infusion or taking blood specimen, in A hospital of Lampung Province. It was a quasi experiment with comparison group design (static group comparism). Sample were neonates aged 0-28 which was applied infusion or taken blood specimen, consist of 16 respondents as group of NNS combination with breast feeding and 16 respondents as group of NNS intervention combination with glucose 30%. Differences of pain response during infusion or taking blood specimen were analyzed by independent sample t-test. The results showed that there was no significant difference between the combination group of NNS with breast feeding and the group of NNS combination with glucose 30% (p=0.076). Based on this study, it was recommended that NNS with breast feeding and NNS with glucose 30%, both can be used as a non-pharmacological therapy management in neonates while applying infusion or taking blood specimen.